Analyzing Public Sentiment on Digital Banks in Indonesia via Social Media X - Arif, Erman; Suherman, Suherman; Widodo, Aris Puji (Aptisi Transactions On Technopreneurship (ATT), 2026)
This study aims to analyze public sentiment towards digital banks in Indonesia, specifically Bank Jago, using data from social media Twitter. Sentiment analysis methods were used to classify tweets into positive, negative and neutral categories. The findings show that public perceptions are generally positive, with a focus on technological innovation and ease of service. However, key complaints related to technical issues and customer service remain noteworthy. Most tweets had neutral to positive sentiments, reflecting a favorable public view of digital banks. These results highlight the importance for digital banks to continuously improve the customer service and technical stability of their apps to maintain a good reputation in the eyes of the public. In addition, the positive sentiments that arise regarding technological innovation can be leveraged to reinforce the bank's image as a modern and efficient institution. Recommendations from this study include developing a more responsive customer support system and improving app stability. With these measures, digital banks can maintain public trust and compete in an increasingly competitive market, as well as increase customer satisfaction and loyalty. This research provides valuable insights for digital bank business strategy in Indonesia.